Determinants for local tumour control probability after radiotherapy of anal cancer. Issue 2 (August 2018) - Johnsson, Anders; Leon, Otilia; Gunnlaugsson, Adalsteinn; Nilsson, Per; Höglund, Peter
Abstract: Background and purpose: Anal squamous cell carcinoma is primarily treated with radiotherapy (RT), but the optimal RT dose for anal tumours of different sizes is not known. The purpose of this study was to identify determinants for local tumour control probability (LTCP). Material and methods: From a large Nordic database 901 patients who received RT for anal cancer between 2000 and 2007 were selected. LTCP was analysed in a series of uni- and multivariable regression analyses. Results: Higher RT dose, female gender and addition of chemotherapy were associated with higher LTCP whereas increasing tumour size, tumour invasiveness (stage T4) and lymph node metastases (N+) were associated with lower LTCP. Male patients needed approximately 10 Gy higher RT dose than female patients for similar LTCP. The addition of chemotherapy corresponded to 5–10 Gy RT dose. Conclusions: Our results basically support current guidelines recommending: (1) lower RT dose in small tumours (<4 cm), (2) higher RT dose larger tumours and in stages T4 and /or N+, (3) Chemo should be used in combination with RT. These results will hopefully constitute the basis for future trials, aiming at individualized RT dosing in patients with anal cancer.